Student Inclusion through Theoretical Reframing - Lamberti, Adrienne (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2022)
In the wake of COVID-19, educators are reconsidering not only conventional methods but also those comparatively recent to pedagogy. However, a change in pedagogical strategy can risk being little more than reactive if its philosophical grounding is unvetted. This piece reconsiders the distributed knowledge framework and its potential for writing program administration and writing instruction. The professional communication discipline has used this framework with a frequent result: privileging expertise at the exclusion of other knowledges. This piece chronicles a writing program administrator’s pre-pandemic use of distributed knowledge, and how pandemic surprises led to a revision of the lens. The post-pandemic frame differently addresses the knowledges at play in a learning community. It works to include more students by including more of each student.